A thermoresponsive three-dimensional fibrous cell culture platform for enzyme-free expansion of mammalian cells. (1st September 2019) - Aladdad, Afnan M.; Amer, Mahetab H.; Sidney, Laura; Hopkinson, Andrew; White, Lisa J.; Alexander, Cameron; Rose, Felicity R.A.J.
Graphical abstract: Abstract: A three-dimensional thermoresponsive fibrous scaffold system for the subsequent extended culture and enzyme-free passaging of a range of mammalian cell types is presented. Poly(PEGMA188 ) was incorporated with poly(ethylene terephthalate) (PET) via blend-electrospinning to render the fibre thermoresponsive. Using primary human corneal stromal stem cells as an therapeutically relevant exemplar, cell adhesion, viability, proliferation and phenotype on this fibrous culture system over numerous thermal enzyme-free passages is described. We also illustrate the versatility of this system with respect to fabricating thermoresponsive fibres from biodegradable polymers and for the culture of diverse mammalian cell types including mesenchymal stem cells, colon adenocarcinoma cells and NIH-3T3 fibroblasts. This thermoresponsive scaffold system combines the advantages of providing a physiologically relevant environment to maintain a desirable cell phenotype, allowing routine enzyme-free passaging and expansion of cultured cells, whilst offering mechanical support for cell growth. The system described in this study presents a versatile platform for biomedical applications and more specifically for the expansion of mammalian cells destined for the clinic. Statement of Significance: The lack of three-dimensional (3D) cell culture environments significantly impacts mammalian cell morphology, proliferation and phenotype in vitro . A versatile, 3D fibrous scaffold system for the extended culture and passaging of a range of clinically-relevant cell types is presented herein. This methodology can be used to fabricate thermoresponsive fibres from polymer blends of any polymer amenable to electrospinning and with a thermoresponsive component. A variety of mammalian cells cultured on the thermoresponsive system were detached from the surface solely by lowering the temperature whilst retaining high viability, a desirable cell phenotype, and supported long‐term cell proliferation over numerous thermal enzyme-free passages. This is a significant advance for in vitro expansion of diverse cell types destined for the clinic.